Problems with serving a Home incanceration - Brašovan Delić, Marina (Glasnik Advokatske komore Vojvodine, 2020)
In the Republic of Serbia, from all alternative criminal sanctions, the courts have in addition to the suspended sentence, most often pronounced the sentence of house arrest. In addition to reviewing the legislation governing the subject area, the author tried to point out the problems that courts and commissioners encounter in practice when executing a house arrest.Inadequate application of regulations governing the execution of a house arrest sentence, along with technical and personnel shortcomings faced by the Commissioner Service within the Directorate for Execution of Criminal Sanctions in the Republic of Serbia, may lead to its partial or temporary impossibility of execution.Using available statistics on imposed criminal sanctions, examining the opinions of judges and the views of commissioners, evaluating data from other research in this area, the author tried to answer the question of whether and how the existing problems of house arrest in Serbia can be get over it. Elimination of formal and technical conditions in enforcement should show the extent to which the imposition of house arrest achieves the goals of general and special prevention, bearing in mind that, in certain situations in practice, the sentence of house arrest remains unexecuted.
Keywords: Keywords: house arrest, the manner of execution of a prison sentence, alternative sanctions, commissioner of execution